Waqf Development in Indonesia: Challenges Faced by Muhammadiyah Waqf Institutions - Fahmi Medias; Eko Kurniasih Pratiwi; Khotibul Umam (Economica: Jurnal Ekonomi Islam, 2019)
Abstract: As a potential financial instrument, waqf has played an essential role in resolving the social problems of the society (ummah). Although Indonesia has long applied the existence of waqf, it has not had an impact on providing an optimal contribution to the welfare of the people. Several studies identified patterns of administration in the management of waqf. The purpose of this study aims to identify and explore the model of empowerment of Mahammadiyah waqf land in Magelang and its challenges in the development of the ummah. The study method used to collect data was descriptive qualitative and interviews, which covered the areas administered by the Mahammadiyah. About 78% of these areas are empowered in the form of educational and worship facilities. However, it was observed that empowerment of the land in Magelang was not optimized due to lack of financial resources, unproductivity, and the presence of incompetent and professional Nazhirs. The solution to these problems is through collaboration with financial institutions in collecting cash equivalents, land specifications, formulating a special legal framework for empowering Muhammadiyah waqf, and training for the development of the capacity of the areas.Abstrak: Sebagai instrumen finansial yang potensial, wakaf memiliki peran penting dalam menyelesaikan permasalahan sosial masyarakat (ummah). Meski keberadaan wakaf sudah lama diterapkan di Indonesia, namun belum berdampak pada memberikan kontribusi yang optimal bagi kesejahteraan masyarakat. Beberapa penelitian mengidentifikasi pola administrasi dalam pengelolaan wakaf. Tujuan penelitian ini adalah untuk mengidentifikasi dan mendalami model pemberdayaan lahan wakaf mahammadiyah di Magelang dan tantangannya dalam perkembangan umat. Metode penelitian yang digunakan untuk mengumpulkan data adalah deskriptif kualitatif dan wawancara meliputi wilayah-wilayah yang dikelola Mahammadiyah. Sekitar 78% dari wilayah tersebut diberdayakan dalam bentuk sarana pendidikan dan ibadah. Namun, teramati bahwa pemberdayaan tanah di Magelang belum optimal karena kurangnya sumber daya finansial, tidak produktif, dan adanya Nazhir yang tidak kompeten dan profesional. Solusi dari permasalahan tersebut adalah melalui kerjasama dengan lembaga keuangan dalam pengumpulan setara kas, spesifikasi tanah, penyusunan kerangka hukum khusus pemberdayaan wakaf Muhammadiyah, dan pelatihan pengembangan kapasitas daerah.